FAKTOR-FAKTOR PELAYANAN KESEHATAN YANG MEMPENGARUHI KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH DR. H. CHASAN BOESOIRIE TERNATE - M. Idham Masuku; Lutfan Lazuardi; Mubasysyir Hasanbasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Complaint is important response from a patientwho has a unique information and valuable for the organizationto improve quality of service and risk management. Thechallenge for the hospital organization now is how to catch andusing information from the patients productive to improve thequality, safety, and it gives the accessibility to care patientsystem or medication. Hospital DR. H. Chasan BoesoirieTernate in 2014 began to hold a counter services for complaintsand information from the public. Based on the data, throughoutthe year 2014 there were four reports of complaints fromexternal customers and internal one complaints fromcustomers. Objective: Knowing the health service factors that affect thesatisfaction of outpatients in RSUD DR. H. Chasan BoesoirieTernate.Methods: This research qualitative eksploratif by using the draftcase study. Subjects is the patients out as much as 16respondents.Results: Existed dissatisfaction patients such as silent, angerand rage, protest, complaint and compare to the hospital, andchoose treated in a hospital. Factors that cause dissatisfactionwith staff that is communication rude, make it harder forpatients, and not discipline time. On the part of management,the waiting time and schedule information are uncertain. On thepart environment, facilities and infrastructure, as well as medicalequipment is not adequate.Conclusion: There is a dissatisfaction as evidence of dissatisfactionpatients. Many factors that influence so that theredissatisfaction patients to service that it receives. Threecomponents in service system in the hospital staff,management and environmental influenced by and each oneanother. It is advisable to see this as positive inputs in order tocarry out quality improvement. The meeting the needs, andexpectations a desire and it will be making customer satisfactionpatients.